Designing an RFID System to Improve Stock Accuracy and Supply Chain Efficiency of PT Bap in the Context of Industry Digitalization 4.0 - Bunga Ayu Pitaloka; Oviyan Patra; Rinto Yusriski; Hendy Suryana (Jurnal Impresi Indonesia, 2025)
This research focuses on designing a Radio Frequency Identification (RFID) system to enhance stock management accuracy and supply chain efficiency at PT Bap , a manufacturing company in the automotive sector. At present, PT Bap  still relies on manual inventory methods that are time-consuming, labor-intensive, and prone to recording errors, leading to inefficiencies in warehouse operations. Considering the large volume of part items, these inefficiencies create significant challenges for productivity and operational effectiveness. To address this, the research adopts a case study approach combined with benchmarking of PT TMMIN, a company that has successfully implemented RFID technology for inventory management. Data collection includes interviews, observations, and documentation of the inventory system at PT Bap , along with comparative studies on RFID adoption at PT TMMIN. The design integrates RFID devices with the existing Warehouse Management System (WMS), automating the inventory process. To strengthen the research foundation, the author also participated in Lean Manufacturing 4.0 training held by the Ministry of Industry of the Republic of Indonesia, which deepened knowledge of digitalization and automation principles in Industry 4.0. The expected outcomes include improved stock accuracy above 90%, inventory time reduction of up to 50%, and lower dependence on manual labor. Ultimately, RFID implementation contributes to operational efficiency and supports digital transformation in the automotive industry